Managing clay minerals in froth flotation—A critical review. (3rd September 2018) - Chen, Xumeng; Peng, Yongjun
ABSTRACT: Clay minerals are widely present in various ore deposits as gangue minerals. The processing of high-clay-content ores is becoming a significant challenge for the mining industry owing to the poor flotation performance caused by the presence of clay minerals. Different types of clay minerals are typically present in ore bodies, and they cause several detrimental effects to flotation that require different treatments. In this article, a comprehensive review of the studies on understanding and mitigating the negative effects of clay minerals in flotation is presented. It starts with a review of the classification and structures of clay minerals commonly occurring in ore deposits and their properties that determine the behavior of clay minerals in flotation. It is followed by a critical review of two main negative effects of clay minerals on flotation, the recent research findings mainly from The University of Queensland group. The first negative effect is the coating of clay minerals on the surface of valuable minerals that decreases the floatability of valuable minerals. The second negative effect is the formation of network structures in the slurry. Depending on the type and strength of the network structure, it can cause either high pulp viscosity or increased gangue entrainment, which reduces the flotation recovery and flotation product grade, respectively. In this section, the mechanisms and key factors behind each negative effect are presented and critically discussed. Then, the approaches and techniques developed to mitigate the different negative effects of clay minerals are reviewed. To conclude, future directions for a more complete understanding of mechanisms and problem solving are recommended.